2021
DOI: 10.3390/ani11010174
|View full text |Cite
|
Sign up to set email alerts
|

Biological Sound vs. Anthropogenic Noise: Assessment of Behavioural Changes in Scyliorhinus canicula Exposed to Boats Noise

Abstract: Despite the growing interest in human-made noise effects on marine wildlife, few studies have investigated the potential role of underwater noise on elasmobranch species. In this study, twelve specimens of small-spotted catshark (Scyliorhinus canicula) were exposed to biological and anthropogenic sounds in order to assess their behavioural changes in response to prey acoustic stimuli and to different amplitude levels of shipping noise. The sharks, individually held in aquariums, were exposed to four experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Previous research has indicated that human-induced noise impacts fish through reductions in movement patterns, feeding success, and slower flight from predators (Payne et al 2014;Leduc et al 2021). Anthropogenic noise also influences elasmobranch behaviour, with sharks increasing time spent swimming and avoiding noisier areas when anthropogenic noise levels exceeded biological noise levels in an aquarium (de Vincenzi et al 2021). Throughout Sydney Harbour, there is substantially more boat traffic during day-light hours.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that human-induced noise impacts fish through reductions in movement patterns, feeding success, and slower flight from predators (Payne et al 2014;Leduc et al 2021). Anthropogenic noise also influences elasmobranch behaviour, with sharks increasing time spent swimming and avoiding noisier areas when anthropogenic noise levels exceeded biological noise levels in an aquarium (de Vincenzi et al 2021). Throughout Sydney Harbour, there is substantially more boat traffic during day-light hours.…”
Section: Discussionmentioning
confidence: 99%
“…The sound mechanism production of spiny lobster associated with the movement of organs (Mulligan & Fischer, 1977). That organ movements indicated that the organism has identified crude oil as a threat and some emit sound in reaction to environmental changes (Bouwma & Herrnkind, 2009;Buscaino et al, 2011;de Vincenzi et al, 2021;Jezequel et al, 2018). In addition, the decrease in sound productivity presumed that P. homarus was under stress or pressure due to crude oil contamination.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of acoustic effects on aquatic organisms, especially fish, show that anthropogenic noise negatively influences both teleost and elasmobranch fish [7,12,13] and directly affects vocal teleost fish, increasing stress, altering their metabolic processes, and negatively affecting all stages of their life activity [5,14,15]. Most fish communicate and hear best precisely in the range of technogenic noise, below 500 Hz, by sensing particle accelerations with their inner ear [16,17].…”
Section: Introductionmentioning
confidence: 99%